Cause of Death in Neonates With Neurological Insults in the Neonatal Intensive Care Unit: Insights From A MITS Pilot Study. (15th December 2021) - Mathew, Mary; Lewis, Leslie; Sreenivas, Athira; Purkayastha, Jayashree
Abstract: Background: Minimally invasive tissue sampling (MITS) of organs has been used as an alternative to complete diagnostic autopsy in countries where refusal for autopsy in newborns is common for sociocultural reasons. There is a paucity of literature regarding the diagnostic utility of MITS of the brain after death in neonates with neurological insults, especially in India. Methods: This was a prospective, preliminary single-center tertiary care hospital study in India, focused specifically on MITS of the brain after neonatal death as a diagnostic tool to identify the various neurological insults. All neonatal deaths with neurological symptoms occurring within the first 30 days of life were enrolled, irrespective of the suspected clinical diagnosis. Results: Sixteen neonates were enrolled after death for MITS of the brain, performed for diagnostic purposes, during the study period from February 2020 to March 2021. Their gestational ages ranged from 26 to 38 weeks. All neonates had either a history of seizures and/or respiratory distress or clinical evidence of sepsis and were on ventilator support. Histopathology in all 16 neonates showed evidence of anoxia, with or without reactive astrogliosis or microgliosis. In 5 neonates with cranial ultrasound evidence of brain hemorrhage, MITS of the brain showed intraventricular hemorrhage, subdural hemorrhage, or intraparenchymal white matter microhemorrhages. Premortem blood culture–proven sepsis was seen in 9 neonates. In all cases (100%), MITS had a good diagnostic yield and was useful to establish the neurological insult in the brain. Conclusions: MITS of the brain provides an accurate and adequate diagnosis and can be an alternative to complete diagnostic autopsy for establishing the cause of death due to neurological insults, especially in low-resource settings where obtaining consent for more invasive procedure is often challenging.